Teori Sosial Konstruktivistik - Bima Nyu (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
This study explores the effectiveness of constructivist theory in enhancing students' understanding and critical thinking skills. Through active participation in constructivist learning, students demonstrated improved abilities to connect concepts with real-world experiences, resulting in better learning outcomes and reduced errors in applying concepts. The findings are consistent with previous research, emphasizing the importance of student-centered learning approaches in achieving deeper understanding. However, challenges were identified in implementing constructivist theory, particularly when teaching abstract concepts and engaging students with limited prior knowledge. Despite these challenges, the benefits of constructivist approaches, which prioritize meaningful and contextual learning, outweigh the drawbacks. The study underscores the need for educators to continue developing student-centered teaching methods while providing the necessary support to overcome potential obstacles.